RESILIENSI DI TEMPAT KERJA PADA KARYAWAN MILENIAL: PERAN MODAL SOSIAL DAN REGULASI EMOSI - Mardianti Mardianti; Rini Indryawati (Universitas Gunadarma, 2023)
Various pressures and problems at work require employees to develop resilience in the workplace. This also applies to millennial employees. Some of the things that are thought to affect resilience in the workplace are social capital and emotion regulation. The purpose of this study was to empirically measure the effect of social capital and emotional regulation on workplace resilience in millennial employees. The participants in this study were 184 millennial employees aged 26 to 41 years who work in Greater Jakarta. The measuring tool used is the resilience at work scale of Winwood (2013), the social capital scale from Wang et al. (2013), and the emotion regulation scale from Radde et al. (2021). Correlation matrix and multiple regression were used to analyze the data. The results of this study show that social capital and emotional regulation jointly affect workplace resilience in millennial employees. Other findings also reveal that the magnitude of the influence of emotion regulation on resilience in the workplace is greater than social capital.